Phraseologisms with the Name of the Bird in Serbian Language - Štrbac, Gordana (Poznańskie Studia Slawistyczne, 2021)
The subject of this paper is phraseology with the name of the bird in its lexical structure (such as crn kao gavran, držati se kao pokisli vrabac, zaplesti se kao pile u kučine, podmetnuti kukavičje jaje etc.). These units were analyzed in order to present the language picture of the animal world of Serbian speakers. The research is based on linguocultural approach to language ‒ Zykova’s conceptual theory of phraseology and culture (Зыкова, 2015). Attention is mostly paid to the problem of motivation of the observed phraseologisms and the phraseological semantic processes. There are several different types of information that motivate the creation of phraseology with the name of the bird as their lexical component: the appearance of the bird, its sound and behavior, as well as its symbolic value.